ROLE OF RURAL WOMEN IN AGRICULTURE AND THEIR TRAINING NEEDS - N. Iftikhar; T. Ali; M. Ahmad (Journal of Animal and Plant Sciences, 2007)
Women play a vital role in crop production like sowing, transplanting, weeding, harvesting and post harvest operations such as threshing, winnowing, drying, grinding, husking and storage. Whereas in livestock production they lookafter animals and do primary medication. They also have to perform domestic chores of cooking, cleaning of house, washing of clothes, taking care of children and fetching of water and fuel. Although they perform all of the above mentioned tasks but due to lack of resources, information sources and technical guidance, they have to meet the challenges of the time. On the other hand, they are deprived of education, nutrition, medication and security. Due to lack of training of rural women, they are lagging behind than the international standards of crop production, livestock management and post harvesting operations resulting low yield of the crops and poor quality of the produce. To probe into the matter, the present study was designed. The Study was carried out in district Bahawalpur. This district consists of five tehsils Hasilpur, Bahawalpur, Khairpur Tamewali, Ahmadpur East and Yazman. Out of which two tehsils were selected randomly and five union councils from each tehsil were again selected on random basis. From each selected union council 2 villages were selected randomly. From each selected village 20 women, who were engaged in agricultural activities, were selected through random sampling, thus making a total of 400 respondents. The data were collected through a pre-tested interview schedule designed for this purpose. The data thus, collected were analyzed and interpreted by using appropriate statistical package to draw the conclusions and to suggest measures for improvement. The study revealed that majority of the respondents were involved in crop production activities such as cotton picking, wheat harvesting, and drying of agri. produce with rank order 1st, 2nd and 3rd.The data depict that majority of the respondents were involved in livestock raising activities like lasi making, milking, milk storage, and watering of animal on top three rank order as calculated above. Whereas, wheat storage, cotton storage and wheat cleaning stood 1st and 2nd order.
Keywords: Rural Women; domestic chore; training needs; crop production; livestock production; cottage industries